2015
DOI: 10.14740/jocmr2303w
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Intralesional Glucocorticoid for Treating Pretibial Myxedema

Abstract: BackgroundPretibial myxedema (PTM) is an uncommon dermopathy associated with autoimmune thyroid diseases. Now it is thought to be autoimmune and its treatment with glucocorticoid is helpful. However, it has not been evaluated.MethodsA prospective randomized controlled trial was performed in 110 patients with PTM to evaluate the efficacy and safety of triamcinolone acetonide with intralesional injection once every 3 days and once every 7 days. Randomization was performed with drawing lots and it was also strati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 17 publications
0
11
0
1
Order By: Relevance
“…Multiple modalities of PTM treatment have been reported that include minimizing risk factors (smoking, obesity), topical steroids, intralesional steroids (triamcinolone, betamethasone) [34], plasmapheresis, intravenous immunoglobulin (IVIg), surgery [35], UVA1, compression bandages, and massage therapy. Glucocorticoid inhibiting TSHR autoimmunity and HA synthesis can lower serum TRAb levels and improve PTM [6,36].…”
Section: Diagnosis and Treatmentmentioning
confidence: 99%
“…Multiple modalities of PTM treatment have been reported that include minimizing risk factors (smoking, obesity), topical steroids, intralesional steroids (triamcinolone, betamethasone) [34], plasmapheresis, intravenous immunoglobulin (IVIg), surgery [35], UVA1, compression bandages, and massage therapy. Glucocorticoid inhibiting TSHR autoimmunity and HA synthesis can lower serum TRAb levels and improve PTM [6,36].…”
Section: Diagnosis and Treatmentmentioning
confidence: 99%
“…When dermatologic manifestations persist, specific therapy may become necessary. For example, studies have shown the efficacy of treating pretibial myxedema with intralesional corticosteroid injections; this treatment approach also applies to patients with similar findings secondary to hypothyroidism (13). Furthermore, treatments to combat hyperhidrosis include topical use of aluminum salts such as aluminum chloride and iontophoresis as firstline approaches.…”
Section: Treatmentmentioning
confidence: 99%
“…Local glucocorticoid application to PTM has been the most effective therapeutic option. Lan et al[ 9 ] have treated PTM using an intralesional glucocorticoid - triamcinolone acetonide acetate - at a concentration of 50 mg/5 mL and the total dose was no more than 100 mg at each session in a patient. Intralesional injection was once every 3 d (regimen 1) or once every 7 d (regimen 2) in PTM patients.…”
Section: Discussionmentioning
confidence: 99%